Proceedings of the 4th International Conference on Industrial Engineering ICIE 2018 - Radionov, Andrey A.; Kravchenko, Oleg A.; Guzeev, Victor I.; Rozhdestvenskiy, Yurij V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights recent findings in industrial, manufacturing and mechanical engineering, and provides an overview of the state of the art in these fields, mainly in Russia and Eastern Europe. A broad range of topics and issues in modern engineering are discussed, including the dynamics of machines and working processes, friction, wear and lubrication in machines, surface transport and technological machines, manufacturing engineering of industrial facilities, materials engineering, metallurgy, control systems and their industrial applications, industrial mechatronics, automation and robotics. The book gathers selected papers presented at the 4th International Conference on Industrial Engineering (ICIE), held in Moscow, Russia in May 2018. The authors are experts in various fields of engineering, and all papers have been carefully reviewed. Given its scope, the book will be of interest to a wide readership, including mechanical and production engineers, lecturers in engineering disciplines, and engineering graduates.
Dynamics of machines and working processes -- Friction, wear and lubrication in machines -- Design and manufacturing engineering of industrial facilities -- Surface transport and technological machines -- Equipment and technology of welding production.
Keywords: Machinery; Manufactures; Multibody systems; Vibration; Mechanics, Applied; Machinery and Machine Elements; Machines, Tools, Processes; Multibody Systems and Mechanical Vibrations